2009
DOI: 10.1007/s10666-008-9186-y
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acid Transport in Water-Saturated Porous Media

Abstract: The presence of humic acid (HA) in water poses environmental problems because it enhances the transport of several contaminants. A series of column experiments was conducted toward studying HA transport in different porous media under various pH, ionic strength, and flow rate conditions. The results showed that decreasing pH and increasing ionic strength increased adsorption and therefore delayed the transport of HA in porous media. However, increasing flow rate accelerated the transport of HA in porous media.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(43 reference statements)
3
6
0
Order By: Relevance
“…Similar observations have been stated in earlier works [25]. The attachment of humic compounds onto the porous media is primarily governed by the pH of the humic acid solution [25]. And furthermore, with a decrease in pH, the reduced sorption of bacteria in the presence of humic acid was found to be more significant and have been mentioned in earlier works [26].…”
Section: Effect Of Humic Acid On the Transport Of Bacteriasupporting
confidence: 89%
See 2 more Smart Citations
“…Similar observations have been stated in earlier works [25]. The attachment of humic compounds onto the porous media is primarily governed by the pH of the humic acid solution [25]. And furthermore, with a decrease in pH, the reduced sorption of bacteria in the presence of humic acid was found to be more significant and have been mentioned in earlier works [26].…”
Section: Effect Of Humic Acid On the Transport Of Bacteriasupporting
confidence: 89%
“…It was observed that with the increase in pH, the attachment/sorption of humic acid to the collector media reduced. Similar observations have been described in earlier studies [25]. The transport of humic acid was found to be affected by a change in pH, ionic strength, and grain size of the matrix.…”
Section: Effect Of Humic Acid On the Transport Of Bacteriasupporting
confidence: 89%
See 1 more Smart Citation
“…The pH of the bulk solution affects the transport behaviour of the HA in the sand columns because all charged surfaces in the system are pH dependent. An acidic pH enhances the retention of HA through decreases in the electrostatic repulsion by protonation of the carboxyl and hydroxyl groups (Kinniburgh et al , 1999; Wei et al , 2010). Hydrogen and Cu 2+ behave as potential‐determining ions on mineral surfaces and soil organic matter and can determine the electrochemical interactions between surfaces and colloids as well as the colloid mobility in porous media (Grolimund et al , 1998; Zhou et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, all these studies do not consider the mechanics of colloid retention in the pore matrix. Recently, Wei et al (2010) have provided evidence of the importance of hydrodynamics in pore water and the role of sorption on transport of HA in sand columns under different electrokinetic conditions, pH and hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%